Stress Distribution on the Fe Based Amorphous Toroidal Transducer Core - Mustafa Göktepe (Advances in Materials Science and Engineering)
The basic principles of sensors are the transmission of energy from one system to another. In general, an electrical signal is produced by the change of a physical property induced by the applied change of a second parameter. In the case of magnetic transducers either the property or the parameter would have a magnetic context. For example, in magnetoelastic toroidal transducers, the induced changes of a physical property, that is, the variation of permeability caused by the applied external force are used to produce a variation in output signal. The linearity, magnitude, sensitivity, and repeatability of the relationship between the output signal of the transducer and the physical property define the quality of the transducer.